Subcutaneous Granuloma Annulare vs. Subcutaneous Vascular Malformations in Children: A Diagnostic Challenge - Besiana P. Beqo; Paolo Gasparella; Christina Flucher; Sebastian Tschauner; Iva Brcic; Emir Q. Haxhija (MDPI AG, 2023)
Objectives. There are various subcutaneous lesions in children and often there is difficulty in obtaining an accurate diagnosis by non-invasive diagnostic procedures. Subcutaneous granuloma annulare (SGA) is a rare granulomatous disease that, even after imaging, is often mistaken for a low-flow subcutaneous vascular malformation (SVM). This study aimed to accurately identify clinical and imaging clues to distinguish SGA from low-flow SVM. Methods. We retrospectively analyzed complete hospital records of all children with a confirmed diagnosis of SGA and low-flow SVM who underwent MR imaging at our institution from January 2001 to December 2020. Their disease history, clinical and imaging findings, management, and outcome were evaluated. Results. Among 57 patients with granuloma annulare, we identified 12 patients (nine girls) with a confirmed SGA diagnosis who underwent a preoperative MRI. Their median age was 3.25 years (range 2-5 years). Of 455 patients diagnosed with vascular malformations, 90 had malformations limited to the subcutaneous area. Among them only 47 patients with low-flow SVM were included in the study and further analyzed. Our SGA cohort had a female predilection (75%) and a short history of lump appearance of 1.5 months. SGA lesions were immobile and firm. Before MRI, patients underwent initial evaluation by ultrasound (100%) and X-ray (50%). Surgical tissue sampling was performed in all SGA patients to establish a diagnosis. All 47 patients with low-flow SVM were diagnosed correctly by MRI. A total of 45 patients (96%) underwent surgical resection of the SVM. A careful retrospective review of imaging findings of patients with SGA and SVM showed that SGA present as homogenous lesions in the shape of an epifascial cap with a typical broad fascial base extending towards the subdermal tissue in the middle of the lesion. In contrast, SVMs always present with variable-sized multicystic or tubular areas. Conclusions. Our study shows clear clinical and imaging differences between low-flow SVMs and SGA. SGA presents characteristically in the shape of a homogenous "epifascial cap," which distinguishes these lesions from multicystic heterogenous SVMs.